2015
DOI: 10.1097/mib.0000000000000406
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of 13-Valent Pneumococcal Conjugate Vaccine in Pediatric Patients with Inflammatory Bowel Disease

Abstract: PCV13 is both immunogenic and safe in pediatric patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Most studies performed in the literature among patients with IBD and rheumatol ogical conditions including patients treated with anti-TNF therapy suggest that pneumococcal vaccine responses are most infl uenced by the presence of an immunomodulator (thiopurine or methotrexate) but not monotherapy with anti-TNF ( 42 ). PCV13 has been shown to be safe and eff ective in children with IBD ( 66 ). Vaccination with both PPSV23 and PCV13 is recommended for those receiving immunosuppressive treatment, to maximize the breadth of serotypes covered (i.e., with PPSV23) and ensure optimal protection against the most common and virulent strains (i.e., with PCV13 ( 10,11 )).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…Most studies performed in the literature among patients with IBD and rheumatol ogical conditions including patients treated with anti-TNF therapy suggest that pneumococcal vaccine responses are most infl uenced by the presence of an immunomodulator (thiopurine or methotrexate) but not monotherapy with anti-TNF ( 42 ). PCV13 has been shown to be safe and eff ective in children with IBD ( 66 ). Vaccination with both PPSV23 and PCV13 is recommended for those receiving immunosuppressive treatment, to maximize the breadth of serotypes covered (i.e., with PPSV23) and ensure optimal protection against the most common and virulent strains (i.e., with PCV13 ( 10,11 )).…”
Section: Summary Of Evidencementioning
confidence: 99%
“…33,34 It has also been shown that the immunological response to vaccination is sometimes decreased in patients exposed to immunosuppressive therapy. [35][36][37] How to treat IBD after a serious infection…”
Section: What Type Of Vaccine For Which Type Of Patients?mentioning
confidence: 99%
“…PCV13 is commonly encountered in pediatric clinics compared to PPSV23 since the conjugate vaccine is fundamental to the primary vaccine series. Banaszkiewics et al demonstrated that pediatric IBD patients have a good response to PCV13, further supporting that T-cell immunity seems to be conserved in IBD patients receiving immunosuppressive therapy and that T-dependent vaccines may be preferential to T-independent vaccines in these patients[ 29 ].…”
Section: Resultsmentioning
confidence: 99%